2015
DOI: 10.2147/ndt.s87359
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine treatment may decrease striatal dopaminergic transporter availability after 8 weeks: pilot SPECT report of three cases

Abstract: Attention deficit/hyperactivity disorder is one of the most common neurodevelopmental disorders. The pathophysiology is thought to involve noradrenaline and dopamine. The role of dopamine transporter (DAT) was evaluated in imaging studies using mostly dopamine reuptake inhibitors. Atomoxetine is a selective noradrenaline reuptake inhibitor. Here we report the results of a pilot study conducted to evaluate changes in striatal DAT after 8 weeks of atomoxetine treatment. Our results suggest that 8 weeks of atomox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Evidence for this was observed in the improvement of blood flow in the prefrontal cortex in three SPECT sessions conducted in our case, following ATX treatment. Previous studies using SPECT of ATX have reported that ATX reduced the bioavailability of DAT in the striatum in adolescents with ADHD ( 36 ) and increased cortical blood flow in the affected area in aphasia after stroke ( 37 ). In the present case, SPECT showed blood flow improvement in both striatum and cortex, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for this was observed in the improvement of blood flow in the prefrontal cortex in three SPECT sessions conducted in our case, following ATX treatment. Previous studies using SPECT of ATX have reported that ATX reduced the bioavailability of DAT in the striatum in adolescents with ADHD ( 36 ) and increased cortical blood flow in the affected area in aphasia after stroke ( 37 ). In the present case, SPECT showed blood flow improvement in both striatum and cortex, which was consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%